Uma proposta original na educação de bem - dotados: ADAV - Associação Milton Campos para desenvolvimento e assistência de vocações de bem dotados em sua primeira década de funcionamento : 1973- 1983 - Cecilia Andrade Antipoff (2010)
ADAV Milton Campos Association for the Development and Assistance of the GiftedVocation is an institution designed to give assistance to the gifted children in the state of Minas Gerais, created under the guidance of the psychologist and pedagogue/educatorHelena Antipoff. The expression gifted child characterizes the individual with superior abilities and potential in relation to the average of the population within the different human areas and characteristics (arts, science, sports). The main aim of this study is to discuss the history of this educational institution over the first ten years of operation (1973-1983) and understand how the gifted children were identified, which was the methodology used in the education of the talents and how the adavianos assess the meaning of having taken part of this experience. Two methodological procedures were conducted: analysis of documents (minutes of meetings; reports; registration forms; mail; published books and bulletins; manuscript accounts, diaries and journals) and semi-structured interviews with four participants of the meetings in the Association, subjected to content analysis. The documents were found in the collections of the CDPHA (Center for Documentation and Research Helena Antipoff), Helena Antipoff Foundation and in the archives of ADAV itself, located in the Fazenda do Rosário Educational Complex, in Ibirité, Minas Gerais. The results indicate that ADAV was an original work, assuming an important role in the development of an educational methodology aimed at the gifted and the development of talents. The definition of gifted surpasses the intellectual issue, in that artistic, creative, sporting and social aspectsare also valued. The identification process proved to be complex, prioritizing the participation of schools through the indication of students who stood out from their classmates. The development of talents took place through meetings which were held as holiday camps whereactivities in different areas were provided with the participation of invited guests on a voluntary basis. The methodology of the meetings was based on the natural experimentation proposed by Alexander Lazursky, adapted by Helena Antipoff, whereby the pupils are placed in an environment rich in stimuli so they can choose the activities best suited to their abilities and interests, under the supervision of educators. The educational principles adopted were: principle of the Escola-Viva (alive school), with immersion in the educational environment and division of daily tasks; association between theory and practice; use of concrete tasks individualized teaching, encouragement to the concern with nature and the general welfare. During the study period were carried out activities in contact with nature, music, literature, library, arts, theatre, handicraft, folklore, sports, games, cooking, science, agriculture, scouting, tours, group dynamics for self-knowledge and group knowledge and lectures given by different professionals, followed by debates. As to the meaning of the adaviana experience for its gifted participants, it was observed that the moments lived in ADAV enabled them to outline a positive view of themselves from the relationships established in themeetings. By interacting with other gifted students, with similar interests and aspirations, made them feel as making part of a group which favored the development of their self-esteem. The results of this research will enable future developments designed for the education of thegifted.